Entre a benevolência que escraviza e a resistência que liberta: ações de liberdade em cartas do século XIX - Fernandes, Taffarel Ramires (2021)
This dissertation aims to produce a description of how freedom is performed in notarial documents from the second half of the 19th century. We used manumission letters written in different parts of the north of Minas Gerais and registered in Montes ClarosMG between 1860 and 1887 to follow network-actors who composed those slave relations and to describe the freedom actions they performed. This research is justified by bringing to the field of Social Psychology reflections regarding a decisive event in the constitution of Brazilian history, slavery in the second reign, under a relational and performative perspective. The theoretical-methodological framework adopted establishes approximations between the Actor-Network Theory (ANT), especially regarding the notions of heterogeneity, multiplicity and performance, and the historiography of Brazilian slavery with regard to the slave family relationship, as well as regarding resistance slave. We follow three network actors in the set of analyzed cards. Initially, we focused on the document “Letter of Liberty”, describing its heterogeneous material constitution, the form of textual arrangement and performance in the slave network, in order to gradually promote the legal transition from slave labor to free labor. Then, we followed the slave masters, since, as they were part of a patriarchal family structure specifically in the North of Minas Gerais, they promoted freedom actions, standing out as benevolent, but keeping the freedmen economically dependent on them. In a third moment, we follow enslaved people in their actions of resistance to perform freedom, based on negotiation, mobilization of the masters' affections, payment and joint actions of the members of an enslaved family. Thus, the argument that freedom is multiple and performative starts from the notion that the heterogeneity of relationships constitutes distinct actors, but that they intersect when they act and are acted reciprocally in a network, and that freedom does not have an original principle , but a relational multiplicity